Statelessness and citizenship : camps and the creation of political space - Redclift, Victoria (London ; $a New York : Routledge/Taylor & Francis Group, 2015)
"This book challenges current views of what it means to be a citizen by focusing on displacement and experiences of space as a political concept. Developing the concept of 'political space', the author analyses how historical processes shape spatial arrangements, informing the identities and political subjectivity available to people. Using Bangladesh as a case study for camp and non-camp based displacement, the book argues that concepts of citizenship are temporally, socially and spatially produced and that therefore crude binary oppositions of statelessness and citizenship are no longer relevant. The book's findings are of relevance to wider problems of displacement, citizenship and ethnic relations worldwide"--
1. Introduction -- 2. Spatial formations of exclusion -- 3. The socio-spatial contours of community -- 4. The crafting of citizenship: Property, territory and the post- colonial state -- 5. The 'social field of citizenship' and the language of rights -- 6. Discourses of 'integration': Capital, movement and 'modernity' -- 7. Conclusion.
"First issued in paperback 2015."
Includes bibliographical references (pages [181]-190) and index.
Keywords: Refugees -- Bangladesh; Stateless persons -- Bangladesh; Citizenship -- Bangladesh; Citizenship; Refugees; Stateless persons; Politics and Government; Bangladesh